An innovative class of aluminum alloys for automotive industry: investigation on their corrosion resistance. Issue 1 (September 2020) - Peter, I; Castella, C; Molina, R
Abstract: Self-hardening aluminum alloys (AlZn10Si8Mg, EN-AC-71100) represent an interesting innovative class of material for the production of automotive and aerospace components with high-mechanical strength and good corrosion resistance. The aim of the present is related to the investigation of the intergranular corrosion resistance of an innovative class of self hardening alloys. Microstructural characterization combined with compositional analysis has been carried out by Optical and Scanning Electron Microscope equipped with Energy X-rays Dispersive Spectroscopy unit. Three-point bending test and Charpy Impact test have been performed and the corrosion resistance of the alloys has been investigated according to standard BS 11846, method B. The susceptibility of the alloy to intergranular corrosion has been assessed evaluating the maximum corrosion depth and the weight loss of the alloy after corrosion test. The results obtained have been demonstrated that the corrosion resistance of the alloy can be achieved by Mg addition.